Use of influenza A viruses expressing reporter genes to assess the frequency of double infections in vitro - Bodewes, R.; Nieuwkoop, N. J.; Verburgh, R. J.; Fouchier, R. A. M.; Osterhaus, A. D. M. E.; Rimmelzwaan, G. F. (Journal of General Virology, 2012)
Exchange of gene segments between mammalian and avian influenza A viruses may lead to the emergence of potential pandemic influenza viruses. Since co-infection of single cells with two viruses is a prerequisite for reassortment to take place, we assessed frequencies of double-infection in vitro using influenza A/H5N1 and A/H1N1 viruses expressing the reporter genes eGFP or mCherry. Double-infected A549 and Madin–Darby canine kidney cells were detected by confocal microscopy and flow cytometry.